Β-Cyclodextrin and graphene oxide co-strengthened AgRu bimetal mesoporous nanozyme: An efficient strategy for visual detection and removal of toxic Hg2+ and Cl−. Issue 5 (October 2022) - Yan, Zhengquan; Xing, Lin; Zhao, Lin; Zhang, Xinyi; Zhang, Yingfan; Tang, Yulian; Zhou, Xuemei; Hu, Lei; Zhu, Nianlei
Abstract: In this work, to efficiently eliminate the threat of toxic Cl − and Hg 2+, a kind of AgRu bimetal mesoporous nanozyme co-stabilized by β-cyclodextrin and graphene oxide (AgRu@β-CD-co-GO) was first developed by a homogeneous redox and assembly method. The mesoporous microstructure and a large number of hydroxyl groups and GO aryl rings endowed AgRu@ β-CD-co-GO with superior peroxidase-mimic performance and enough active spots to adsorb more toxic Cl − and Hg 2+ . Under optimal conditions (pH 4.0, 350 μL 1.5 mM TMB and 200 μL 1.0 M H2 O2 and incubated for 30 min at 25 °C), AgRu@ β-CD-co-GO could accelerate the oxidation of colorless 3, 3′, 5, 5′-tetramethylbenzidine (TMB) into blue oxTMB in the presence of H2 O2 . Toxic Cl − or Hg 2+ would exclusively alter its peroxidase-like activity, accompanied with the characteristic UV–vis absorption intensity at 653 nm ( A 653 ) decreased and color changed from blue to colorless. AgRu@ β-CD-co-GO was successfully applied for visual detection of Cl − and Hg 2+ and enriched removal of them after their detection. The detection limits were low to be 3.2 × 10 −10 mol∙L −1 for Hg 2+ and 6.4 × 10 −8 mol/L for Cl − . After detection, more than 94.9% Hg 2+ and 93.8% Cl − could be removed by only a simple filtration. The mechanisms for peroxidase-mimic activity of AgRu@ β-CD-co-GO and its exclusive recognition of Hg 2+ and Cl − were proposed. Graphical Abstract: ga1 Highlights: Mesoporous AgRu@ β-CD-co-GO nanozyme was developed by a homogeneous redox method. The peroxidase-like activity could be exclusively altered by Cl − or Hg 2+ with visual color change. AgRu@ β-CD-co-GO was applied for visual monitoring and removal of Cl − or Hg 2+ in practice. The recognition mechanism was confirmed to form Ag-Ru amalgam or chloride on the surface of AgRu@ β-CD-co-GO.